URGENSI DAN STRATEGI PEMANFAATAN KOLEKSI REFERENSI BAGI PEMUSTAKA DI PERPUSTAKAAN PERGURUAN TINGGI - Kartika Dewi, Desak Putu Sukma; Haryanti, Ni Putu Premierita; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 2 No 1 (2022), 2022)
The reference collection is one of the important collections in the library, including the university library. College libraries in addition to providing reference collections also specifically provide reference services to assist users in using reference collections. The goal of this paper is to deliver a strategy for the use of reference collections that can be applied by libraries to users. The research method used is literature study. Reference collections in university libraries are rarely used by users because many people have turned to looking for information on the internet instead of reading directly to the library. The strategies that can be carried out include: educating users on how to access or introducing reference collections to students, promoting reference collections by utilizing social media and always providing the latest and most up-to-date reference collections so that users are interested in using reference collections. Keywords : library strategy, library collection, reference collection